Understanding Learners’ participative motivation in Reading Challenge (International Conference on Computers in Education, 2011)
The study is based on related motivation theory to explore the learners' participative motivation in an English reading contest. Total 30 winners in high school are subjects in this study. After analyzing interview content, we divided learners' participative motivation in contest into: participative intrinsic motivation, participative extrinsic motivation, and participative interpersonal motivation. This study also presents the future work for further research.